Combined therapy of arterial hypertension: focus on pleiotropic effects - D. B. Nebieridze (Кардиоваскулярная терапия и профилактика, 2007)
The article is focused on the importance of adequate blood pressure (BP) control in arterial hypertension, as well as on pleiotropic treatment effects. The latter are especially important in combined therapy, that, as a rule, is needed to achieve target BP levels. The principal pleiotropic effects include metabolic action and vasoprotection via endothelial function improvement. Tarka medication includes two well-known agents - verapamil SR (180 mg) and trandolapril (2 mg). Tarka therapy facilitates not only prolonged BP control, but also vasoprotection and organ protection, without adverse metabolic effects.